D‐Peptides as Recognition Molecules and Therapeutic Agents. Issue 4 (3rd June 2016) - Liu, Min; Li, Xue; Xie, Zuoxu; Xie, Cao; Zhan, Changyou; Hu, Xuefeng; Shen, Qing; Wei, Xiaoli; Su, Bingxia; Wang, Jing; Lu, Weiyue
Abstract: Over recent years, D‐peptides have attracted increasing attention. D‐peptides increase enzymatic stability, prolong the plasma half‐life, improve oral bioavailability, and enhance binding activity and specificity with receptor or target proteins, in comparison with the corresponding L‐peptide. Therefore, D‐peptides are considered to have potential as recognition molecules and therapeutic agents. This review focuses on the design and application of D‐peptides with biological activity. Abstract : The retro‐inverso peptide is composed of D‐amino acids assembled in the reverse order to that of the parent L‐sequence. Due to similarities, in terms of side‐chain topology with its parent L‐peptide, the retro‐inverso peptide has biological activity. In addition, it can resist protease degradation. Therefore, retro‐inverso peptides have gained widespread interest as recognition molecules and therapeutic agents in the fields of cancer, infectious viral diseases, and immune and metabolic diseases, as well as central nervous system diseases.